Keterkaitan Konten Reels Instagram pada Minat Beli Pengikut @Cannie.Gift pada Aplikasi Instagram - Elisabeth Mellyana Dea Maharani; Hudi Santoso; Enden Darjatul Ulya; Rici Tri Harpin Pranata (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The rapid growth of short-video features on social media has encouraged businesses to optimize Instagram Reels as a digital marketing tool to stimulate consumer purchase intention. However, empirical evidence on how Reels content influences purchase intention in emotionally driven businesses such as florist and gift shops remain limited. This study aims to analyze the relationship between Instagram Reels content and the purchase intention of followers of the Cannie Gift and Florist Instagram account. A quantitative explanatory approach was employed, with data collected from 92 active followers using purposive sampling. Reels content was measured through visual-audio quality, creativity and message clarity, posting frequency, and interactivity, while purchase intention was assessed through product interest, information-seeking behavior, willingness to buy, and recommendation tendency. Data were analyzed using Spearman Rank correlation after validity and reliability tests confirmed the robustness of the instrument (Cronbach’s Alpha = 0.812). The results indicate a strong and significant positive relationship between Reels content and purchase intention (? = 0.687; p < 0.001). Among the indicators, presentation style and visual-audio quality showed the strongest association with purchase intention. These findings demonstrate that well-designed and engaging Reels content plays a crucial role in enhancing consumer interest and encouraging purchasing intentions in florist and gift businesses.